Effects of a single tDCS with mirror therapy stimulation on hand function in healthy individuals - Wójcik, Małgorzata; Vlček, Přemysl; Siatkowski, Idzi; Grünerová-Lippertová, Marcela (Frontiers in Human Neuroscience, 2025)
IntroductionTranscranial direct current stimulation (tDCS) is a non-invasive neuromodulatory technique that has garnered significant interest for its ability to modulate cortical excitability and brain function. The technique involves the application of a weak electrical current through electrodes placed on the scalp, which influences neuronal membrane potential and alters synaptic plasticity.MethodsThe following research hypotheses were defined: (1) a single tDCS stimulation of the motor cortex on the left side in combination with mirror therapy (MT) improves the function of the right hand which is dominant; and (2) a single stimulation in combination with MT for the dominant hand (right hand) also improves the function of the non-dominant hand (left hand). A total of 106 subjects aged 51.5 ± 12.02 participated in the study, including 63 women and 43 men. We used tests for assessment before and after tDCS stimulation: Tapping Tablet, Reaction Test on a tablet, Nine Hole Peg Test (NHPT), exercises for dominant hands, tDCS stimulation with MT.ResultsThe obtained results of this conducted study, although preliminary, seem to indicate that in each of the analyzed age groups in men and women, a single tDCS stimulation in combination with MT directly improved the function of the dominant hand and indirectly improved the function of the non-dominant hand.DiscussionThe use of tDCS stimulation appears promising to improve hand function.